2021
DOI: 10.3352/jeehp.2021.18.24
|View full text |Cite
|
Sign up to set email alerts
|

Changes in academic performance in the online, integrated system-based curriculum implemented due to the COVID-19 pandemic in a medical school in Korea

Abstract: Purpose: This study aims to examine how students' academic performance changed, based on the test results of 16 integrated courses conducted in 3 semesters at Hanyang University College of Medicine that underwent a transition to online learning after COVID-19 in Korea. Methods: For the 16 required courses that included an integrated system-based curriculum that runs for t3 semesters, the major examination's raw scores were collected for each student. Percent-correct scores were used in the subsequent analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…However, a previous study documented that the type II error rate was increased after Bonferroni correction (Perneger, 1998 ). To avoid the risk of type I and type II errors, the Cohen’s d value was presented accompanied with the P ‐value in the current study (Kim et al, 2021b ). Third, the questionnaire was designed without balancing positive and negative indicators, which may create a bias for its interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous study documented that the type II error rate was increased after Bonferroni correction (Perneger, 1998 ). To avoid the risk of type I and type II errors, the Cohen’s d value was presented accompanied with the P ‐value in the current study (Kim et al, 2021b ). Third, the questionnaire was designed without balancing positive and negative indicators, which may create a bias for its interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study documented that the type II error rate was increased after Bonferroni correction (Perneger, 1998). To avoid the risk of type I and type II errors, the Cohen's d value was presented accompanied with the P-value in the current study (Kim et al, 2021b).…”
Section: Limitations Of This Studymentioning
confidence: 97%
“…16 However, a study in Korea that looked at the academic performance of students in 19 different courses found that the average test scores decreased for most online courses. 17 Various reasons were suggested for this decline, such as the sudden transition to online classes, the fact that most of the faculty did not have proper training for online classes, and the lack of technical support. 17 Moreover, another study showed that even though students had more time to study when courses were delivered online, the majority of them preferred traditional teaching for better understanding of the course materials and topics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, students felt that the in-person session was preferable over a hypothetical virtual session to interact with their classmates and learn essential ECG concepts, supporting the idea that medical students continue to prefer learning new material in an in-person setting [ 13 ]. Furthermore, previous studies demonstrate a decline in student performance with the shift to virtual learning during the pandemic, thus emphasizing the importance of safe and supportive in-person learning sessions in pre-clerkship medical training [ 14 , 15 ].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%